Readiness Analysis of Infrastructure Smart City in Wonogiri Regency - Singgih Manggalou; Binti Azizatun Nafi’ah (Nusantara Science and Technology Proceedings, 2022)
The development of the world's digital governance era has reached the development of smart city 4.0. Not many cities can make that happen. In Indonesia, the movement towards smart cities is still starting to be echoed. So it is necessary to prepare and have the will of the region to implement a smart city because of the difficulty in preparing to implement a smart city. Wonogiri Regency is one of the districts selected for smart city implementation because the achievement of the Electronic-Based Government System (SPBE) indicator has increased. The purpose of this study was to analyze the readiness of infrastructure for a smart city master plan in Wonogiri Regency. This research is a qualitative type with data collection techniques through in-depth interviews with 8 purposively selected informants. The researcher found that the readiness of infrastructure was in good condition.